2015
DOI: 10.1136/bcr-2015-212428
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected finding of a splenic infarction in a patient with infectious mononucleosis due to Epstein-Barr virus

Abstract: SUMMARYThe authors present a case of a 24-year-old man with infectious mononucleosis (IM) due to Epstein-Barr virus (EBV). Among his symptoms, he reported abdominal pain in the upper left quadrant. An abdominal ultrasound and CT revealed an extensive splenic infarction. During the acute stage of this disease, the thrombophilic screening revealed reduced free protein S and elevated factor VIII, with normalisation on reevaluation 6 weeks later. Splenic infarction is a very rare complication of IM due to EBV but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
14
0
3
Order By: Relevance
“…Other causes revolve around the presence of a transient hypercoagulable state, caused by a decrease in the levels of protein C and protein S, compounded by an increase in the size of the spleen, resulting in an infarct [10,11]. However, activated protein C resistance was not checked [12]. A case report was also seen to have positive antiphospholipid antibodies and another with elevated factor Ⅶ [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other causes revolve around the presence of a transient hypercoagulable state, caused by a decrease in the levels of protein C and protein S, compounded by an increase in the size of the spleen, resulting in an infarct [10,11]. However, activated protein C resistance was not checked [12]. A case report was also seen to have positive antiphospholipid antibodies and another with elevated factor Ⅶ [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, activated protein C resistance was not checked [12]. A case report was also seen to have positive antiphospholipid antibodies and another with elevated factor Ⅶ [12,13]. Hence, further studies will be needed to establish the hypothesis of transient hypercoagulable state leading to splenic infarct.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 patients, nine underwent follow-up imaging: CT in four cases [van Hal et al, 2005;Gang and Kim, 2013;Kobe et al, 2013;Li et al, 2014], US in three [Cull and Stein, 2012;Gavriilaki et al, 2013;Machado et al, 2015], MRI in one [Breuer et al, 2008], and one case did not mention the imaging method [Trevenzoli et al, 2001]. Seven patients showed improvement in a median follow-up time of 67 days (range, 30-128 days) [Trevenzoli et al, 2001;van Hal et al, 2005;Cull and Stein, 2012;Gang and Kim, 2013;Gavriilaki et al, 2013;Kobe et al, 2013;Machado et al, 2015]. However, one patient had aggravated findings on follow-up MRI after 10 days [Breuer et al, 2008], while another patient had no change on follow-up CT performed within 7 days [Li et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…In the case presented in this study, coagulopathy test results were within the normal range. However, some cases have suggested that coagulopathy is associated with splenic infarction in IM, including a case with decreased activity of proteins C and S, but activated protein C resistance not checked [Breuer et al, 2008;Gang and Kim, 2013;Machado et al, 2015]; a case of positive lupus anticoagulant and anticardiolipin antibodies [Hunt et al, 2010;Cull and Stein, 2012]; a case of positive antiphospholipid antibodies [van Hal et al, 2005;Cull and Stein, 2012]; and a case with increased factor VIII [Machado et al, 2015]. In most cases, however, thrombophilic study results were unremarkable or not available.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the active genes influence different molecular and cell cascades, in particular, the signal activity through the transcription factor NF-kB which is of particular importance for latency maintenance. A state of latency is reversible, mechanisms, causing viral genome transcription reactivation, are studied insufficiently [22,23].…”
Section: Introductionmentioning
confidence: 99%